Social media crisis communication in racially charged crises: Exploring the effects of social media and image restoration strategies - Triantafillidou, Amalia; Yannas, Prodromos (Computers in human behavior, 2020)
Using a 3 × 4 between-subjects experiment, the present study delineates the effects of social media platforms (Facebook, Twitter, and Instagram) and image restoration strategies (denial, reduction of offensiveness, corrective action, and mortification) on post-crisis reputation evaluations, positive social media engagement, and offline behavioral intentions, in the context of a fictitious hotel company facing a racially charged crisis. The results indicate that Twitter was more effective than Facebook and Instagram in terms of restoring a company's post-crisis reputation, triggering positive social media engagement with the message, and enhancing the offline behavioral intentions of users. Irrespective of the social media platform on which the message was disseminated, corrective action proved to be the most engaging strategy, triggering more online reactions such as likes, shares, and positive comments. This study also sheds light on the interplay between the dependent variables (post-crisis reputation, positive social media engagement, and offline behavioral intentions) and social media usage frequency. Important implications for crisis managers facing racially charged crisis are derived. •Twitter resulted in higher reputation, SM engagement, and behavioral intentions.•The strategy of corrective action resulted in higher SM engagement.•No interaction effect was found between the type of SM and response strategy.